Antimicrobial Activity of Zinc Oxide Nanoparticles Synthesized Using Bunium Persicum Plant Extract - Maryam Bakhti; Fahimeh Baghbani-Arani; Parisa Shishesaz; Masoumeh Mahdavi-Ourtakand (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2022)
Background and Objectives:  Zinc oxide nanoparticles as a new generation of antimicrobial substances, are of interest in medicine and food industry. This study aims to investigate the antimicrobial effect of zinc oxide nanoparticles synthesized by using Bunium persicum plant extract. Methods: In this study, the biosynthesis of zinc oxide nanoparticles by Bunium persicum extract was performed by zinc acetate precursor. The structure and morphology of the synthesized nanoparticles were characterized by field emission scanning electron microscopy, Fourier transform infrared spectroscopy, X-ray diffraction, and Zetasizer. Then, the antimicrobial effects of synthesized nanoparticles against some gram-positive and gram-negative bacteria were assessed by the disk diffusion and broth microdilution methods. Results: The synthesized zinc oxide nanoparticles had spherical to polygonal shapes with an average size of 100 nm. The minimum inhibitory concentration of nanoparticles against the study bacteria was in range of 3.125 to 25 μg/mL. Conclusion: The extract of Bunium persicum plant can be a good candidate for the green synthesis of zinc oxide nanoparticles with significant antibacterial effects.